Nicaragua : Report on Observance of Standards and Codes; FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2010)
In 2008, Nicaragua introduced legislation criminalizing money laundering (ML) and the financing of terrorism (FT) that is generally adequate, except for some key deficiencies. The Antimony Laundering and Combating the Financing of Terrorism (AML/CFT) preventive measures for the regulated financial sector, including its supervision, is broadly in compliance with the international standard, but the financial cooperative sector is not regulated. There was no evidence of FT risk, and there have been no suspicious transaction reports or investigations in this regard. Nicaragua does not have an FIU and generally lacks an adequate AML/CFT institutional framework.